Study on Procedures for Acceptance of Waste in Landfill. (2016) - Morar, Florica; Bucur, Bogdan; Stoica, Anisoara
Abstract: This paper intends to conduct a study on the classification of sludges resulted from the treatment plants in a class storage according to the procedures for accepting waste storage. Waste that can be stored on a specific location should be reflected in the environmental authorization of the warehouse. It is necessary for the waste generators and operators warehouses follow the procedures for accepting waste for storage because it helps to prevent or reduce negative effects on the environment, particularly pollution of surface water, groundwater, soil, air and the any risk to human health, the duration of operation of the deposit and after its expiry.There were determined heavy metals and anions from mud samples taken from a company that produces car parts to determine what grade of deposits falling.